Real-Time Telemetry Based Monitoring System for Energy Efficiency Evaluation of Scheduled Dimming in Office Corridor Lighting - Muhammad Risqi Nuryana; Veronica Windha Mahyastuty; Ridwan Satrio Hadikusuma (Jurnal Sistem Cerdas, 2026)
In many office buildings, corridor lighting systems are commonly operated at full brightness continuously, regardless of occupancy conditions, resulting in unnecessary energy consumption. This study proposes and evaluates a real-time telemetry-based monitoring system to assess the energy efficiency of a scheduled dimming strategy for office corridor lighting. The developed system integrates dimmable LED luminaires with a telemetry unit capable of transmitting real-time illuminance and energy consumption data for monitoring and analysis. A time-based dimming schedule of 25%, 50%, and 75% output levels was implemented in an office corridor environment. Illuminance measurements were collected at five different points along the corridor, while electrical energy consumption was recorded continuously over a seven-day observation period through the telemetry monitoring platform. The results indicate that even at the lowest dimming level (25%), the corridor maintained an average illuminance of 100 lux, which remained within acceptable lighting standards for pedestrian circulation. Telemetry data further demonstrated that the scheduled dimming strategy reduced weekly energy consumption by approximately 64% compared to continuous full operation (0.711 kWh reduced to 0.253 kWh). These findings confirm that real-time telemetry monitoring enables accurate performance evaluation of lighting control strategies while ensuring compliance with visual comfort requirements. The study highlights the potential of telemetry-based lighting monitoring systems as an effective approach to optimize energy use, minimize over-lighting, and support data-driven energy management in office buildings.